UTILIZING CONTEMPORARY MEDIA TO CURB RAPE ISSUES IN NIGERIA - Oleh, Cyril Onyemaechi (The Gender Truth Journal, 2024)
Rape is a form of sexual violence against the male or female gender. Reports abound on the issue of rape in Nigeria. Some factors such as uncensored exposure to content on the internet such as Facebook, Instagram, Tik Tok, have been identified as helping to sustain the culture of rape in society. Nevertheless, this paper argues that despite posing a series of social challenges such as being veritable platforms for exposure to pornography and other anti-social behaviours, contemporary media platforms such as WhatsApp, Facebook, Instagram, and Tik Tok, still present viable platforms for reducing issues of rape in Nigeria. The penetrative influence of contemporary media among citizens makes it a possible platform for advocacy campaigns against rape. Using secondary sources of data, the paper seeks to determine how the identified platforms can conversely be used to achieve the goal of reducing incidences of rape in Nigeria. Employing the Agenda Setting Theory, the paper suggests how contemporary media can be leveraged to reduce rape issues while providing victims of rape the needed succor. The paper concludes that efforts to reduce rape issues in Nigeria must be intentional and approached through a well-fashioned contemporary media strategy.